Torsed and amputated ovary in the canal of Nuck in a 3-year-old girl: A case report - Yohei Sanmoto (Elsevier, 2024)
Introduction: Amputated ovaries caused by prenatal torsion often remain asymptomatic, but their natural history is not fully understood. Case presentation: A 3-year-old girl presented with swelling in the right inguinal region. She had been diagnosed with a cyst on her left ovary during the fetal period. Postnatal ultrasound examination revealed necrosis and solid-cystic transformation of the left ovary. The necrotic ovary decreased in size over time without intervention. At the time of consultation, a nonreducible, firm, and elastic mass was found in the right inguinal region. Initially, a hydrocele of the canal of Nuck was suspected, but an ultrasound examination showed that the mass had heterogeneous solid components. Given the distinctive clinical progression, an amputated ovary was suspected, and surgical exploration was carried out. During the operation, an initial laparoscopic examination revealed the absence of the left ovary, as well as bilateral inguinal hernias. Since the mass could not be manually reduced back into the abdominal cavity, a small incision was made on the right inguinal region to directly visualize it and remove it. The inguinal hernias were repaired laparoscopically. The mass was formed predominantly of necrotic tissue partially calcified, and there was no viable ovarian tissue. Clinical and pathological findings strongly suggested that the torsed necrotic left ovary had migrated into the canal of Nuck and presented as an inguinal mass. Conclusion: A torsed necrotic ovary may invade the canal of Nuck and potentially present as an inguinal mass.